The Use of a Sheathless Basket via Miniature Ureteroscopes. Issue 3 (1995) - Watson, Graham
Abstract : The conventional use of a basket involves a metallic wire section that is contained within a polythene sheath. The wire basket can be withdrawn or protruded from the sheath using a handle. The advantage of this system is that the basket can be kept shut or open at will within the ureter. Thus one can keep the basket closed in order to maneuver the basket past a stone before opening it above the stone. With the development of efficient and safe lithotripsy modalities becoming widely available and with miniaturization of these and the ureteroscopes, it is becoming less common to dilate the ureter. Therefore it is not frequently possible to extract a stone intact. Baskets still can be used secondarily to extract the fragments. It is possible to use the basket wire without its sheath. The ureteroscope channel effectively becomes the sheath, and the basket opens immediately on protruding it beyond the ureteroscope. This has the following advantages: ( a ) A larger-diameter basket wire can be introduced. The very small baskets of 2F and 3F used via miniature ureteroscopes are very flimsy. When the sheath is removed, it becomes possible to use an otherwise 3F basket via a 2F channel. ( b )The operator can work the basket usingjust two fingers close to the instrument channel port. This is more ergonomic than working an opening mechanism at the end of the basket, because this latter system takes the operator's hand away from the instrument. ( c ) The basket can be detached more readily from the ureteroscope, should it become, impacted together with a stone within the ureter. This makes it possible to reinsert the ureteroscope alongside the basket and fragment the stone within the basket, provided that there is no reinforced section to the inner wire at the handle.